Leilões eletrônicos reversos multiatributo : uma abordagem de decisão multicritério como instrumento de agregação de valor aos processos de compras do setor público brasileiro - Menezes, Ronald do Amaral (2003)
Auctions are secular institutions used in the commercial relationships among individuaIs and organizations. They provi de greater flexibility to the processes of determination of prices and allocation of goods, increasing the space for negotiations among buyers and sellers. In the Internet, they have been used, in a growing way, in B2B and G2B electronic commerce, mostly through the model of reverse auctions. However, its unidimensional aspect reduces the negotiations to the variable price, producing, many times, bad results. In the Brazilian case, the Federal Government launched Comprasnet, an Internet public emarketplace, through which public organizations acquire goods and services from registered suppliers. Considering alI the available bidding modalities, 'Electronic Pregão' stands out, as an unidimensional reverse auction, based on price, through which suppliers dispute for contracts of the public administration. In the present work, the author proposes a multicriteria decision-making approach, based on Multi-attribute Utility Theory, as an alternative for the adoption of multi-attribute reverse auctions, adding value to Brazilian Public Buying Organizations.